PENGARUH PROFITABILITAS, LIKUIDITAS DAN INFLASI TERHADAP HARGA SAHAM PERUSAHAAN INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017 S.D. 2021 - Devi Rahmadani; Imawati Yousida; Noor Ritawaty; Suzi Suzana (Jurnal Ilmu Ekonomi dan Bisnis, 2023)
Abstract: This study aims to determine the effect of profitability, liquidity and inflation on stock prices of food and beverage companies listed on the Indonesia Stock Exchange for the period 2017 to 2017. 2021. These variables have different indicators such as profitability which has an indicator of return on assets, liquidity which has an indicator of the current ratio and inflation which has an indicator of the consumer price index. The type of data used in this study is secondary data in the form of company financial statements, stock prices and consumer price index. To measure the inflation rate, data can be obtained by accessing the websites of the Indonesia Stock Exchange and the Central Bureau of Statistics. The analysis technique is using purposive sampling with a population of 72 and a sample of 18. The results of this study partially show that profitability has a significant effect on stock prices, liquidity has a significant effect on stock prices and inflation has no effect on stock prices. With a percentage of 50.2% while 49.9% is influenced by other variables Keywords: Profitability, Liquidity and Inflation